Pengaruh Kualitas Produk, Harga dan Promosi Terhadap Keputusan Pembelian Konsumen Pada Produk Karawo di Kota Gorontalo - Agustina Ishak, Rahayu; Laekkeng, Mursalim; Amir; Mahmud, Amir (STIM-LPI Makassar, 2024)
This research aims to analyze the influence of product quality, price and promotion on purchasing decisions for karawo products in Gorontalo City. This population consisted of 50 people and used a simple random sampling technique. In this case, to confirm the research hypothesis which was collected through a questionnaire and then analyzed using multiple linear regression analysis techniques supported by the SPSS (Stratistical Product and Service Solutions) application 22. The research results show that: (1) Product quality has a positive and significant effect on the decision to purchase karawo; (2) Price has a negative and insignificant effect on purchasing decisions for Karawo products; (3) Promotion has a positive and significant effect on the decision to purchase karawo. Research recommendations: (1) High product quality in the future must be maintained properly, take advantage of developments in digitalization to improve product quality in line with current developments and the need for special education and training for karawo craftsmen to be able to develop products; (2) When determining prices, you should pay attention to the suitability between the quality and benefits of the product being marketed and the price; (3) Cooperation between stakeholders is needed to be able to promote Karawo products